Long-term seizure outcome and risk factors for recurrence after extratemporal epilepsy surgery - McIntosh, Anne M.; Averill, Clare A.; Kalnins, Renate M.; Mitchell, L. Anne; Fabinyi, Gavin C. A.; Jackson, Graeme D.; Berkovic, Samuel F. (Epilepsia (Copenhagen), 2012)
Summary Purpose:  We aimed to assess long‐term seizure outcome and risk factors for seizure recurrence in a cohort of patients who have undergone extratemporal resection for management of refractory seizures. Methods:  Eighty‐one patients underwent extratemporal resection at Austin Health, Melbourne, Australia (1991–2004). Seizure recurrence was any postoperative disabling seizure (complex partial seizure [CPS] ± secondary generalization). Multivariate Cox proportional hazards regression models examined potential preoperative and perioperative risk factors and the risk associated with early postoperative seizures (≤28 days postsurgery). The change between preoperative and postoperative seizure frequency was also measured. Key Findings:  Median follow‐up was 10.3 years (range 1–17.7). The probabilities of freedom from disabling seizures (on or off antiepileptic medication) were 40.7% (95% confidence interval [CI] 30–51) at 1 month, 23.5% (95% CI 15–33) at 1 year, and 14.7% (95% CI 8–23) at 5 years postoperative. Reduction of disabling seizures to at least 20% of preoperative frequency was attained by 57% of patients at 5 postoperative years. Of the preoperative/perioperative factors, focal cortical dysplasia (FCD) type 1 (hazard ratio [HR] 1.90, 95% CI 1.08–3.34, p = 0.025) and incomplete resection (HR 1.71, 95% CI 1.06–2.76, p = 0.028) were independent recurrence risks. After surgery, an early postoperative seizure was the only factor associated with higher risk (HR 4.28 [2.42–7.57], p = 0.00). Significance:  Distinction between subtypes of focal cortical dysplasia, which can be made using magnetic resonance imaging (MRI) criteria, may be useful for preoperative prognostication. Early seizures after surgery are not benign and may be markers of factors that contribute to seizure recurrence. Most patients achieve substantial reduction in seizure frequency. Further study of the significance of this reduction in terms of surgical “success” or otherwise is required.